2016
DOI: 10.1080/01443410.2016.1150423
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimisation and its relation to class relational climate and class moral disengagement among school children

Abstract: The aim of the present study was to examine whether class climate and class moral disengagement each contribute to explain different levels of victimisation among classes. Eight-hundred-and-ninety-nine children from 43 Swedish elementary school classes participated in the current study. Class moral disengagement, class relational climate and peer victimisation were assessed by a self-report questionnaire. In order to account for the clustered nature of the data with students nested within school classes, a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
2
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 64 publications
1
37
2
4
Order By: Relevance
“…The findings presence of Islamic moral horizontal values is the association with behavior of the student. These findings consist of previous studies reported by Lan et al, (2008), and Thornberg et al, (2017) that report the moral values in the school's context are associated with the behavioral students. According to Leming (2006) the research on values clarification indicated that little or no confidence is warranted regarding its potential curricular effectiveness.…”
Section: E Discussionsupporting
confidence: 87%
“…The findings presence of Islamic moral horizontal values is the association with behavior of the student. These findings consist of previous studies reported by Lan et al, (2008), and Thornberg et al, (2017) that report the moral values in the school's context are associated with the behavioral students. According to Leming (2006) the research on values clarification indicated that little or no confidence is warranted regarding its potential curricular effectiveness.…”
Section: E Discussionsupporting
confidence: 87%
“…School psychologists should advocate and promote a positive moral atmosphere in the school and a prosocial moral development among students by their participation in school‐based antibullying teams, consultations with educators, and direct interventions with bullies. A positive moral atmosphere in schools and classrooms with warm, caring, and just relationships among students and between teachers and students has been found to be associated with greater moral development (Power & Higgins‐D'Alessandro, ; Watson, ) and less bullying and peer victimization (Konold et al., ; Thornberg, Wänström, & Pozzoli, ). With reference to Watson (), crucial components for building a positive moral atmosphere in schools and classrooms that promote moral competence and prosocial behavior are: (a) warm, caring, supportive, and mutually trusting teacher–student relationships; (b) classrooms that are characterized as caring and democratic in which each student's needs for competence, autonomy, and belonging are met; (c) opportunities for students to discuss, develop, and refine their understanding of moral values and how to integrate them into everyday school life; and (d) teachers who give structure, guidance, and proper responses to misbehavior, particularly by induction and reasoning.…”
Section: Limitationsmentioning
confidence: 99%
“…Če učenci poročajo o slabšem odnosu z učitelji, to vpliva na to, da so bolj ranljivi za doživljanje psihičnega distresa ob doživljanju viktimizacije (Sulkowski in Simmons, 2017). Pri negativnih odnosih med učenci in učitelji je pomemben tudi vpliv na negativno razredno klimo, ki posredno vpliva na pojav viktimizacije v razredu (Thornberg, Wänström in Pozzoli, 2017).…”
Section: Dejavniki Na Ravni Odnosov Z Učiteljiunclassified